Health-related quality of life of adolescents with type 1 diabetes mellitus - Maria Amélia de Souza; Roberto Wagner Junior Freire de Freitas; Luciane Soares de Lima; Manoel Antônio dos Santos; Maria Lúcia Zanetti; Marta Maria Coelho Damasceno (Universidade de São Paulo, 2019)
Objective: To evaluate the health-related quality of life of adolescents with type 1 diabetes mellitus, associating it with socio-demographic, clinical and biochemical variables. Method: Cross-sectional study with 92 adolescents with type 1 diabetes mellitus. A form containing socio-demographic, clinical and biochemical variables was used, as well as the Diabetes Quality of Life for Youths questionnaire. Descriptive statistics and logistic regression were used for analysis. Results: Regarding socio-demographic variables, economic class showed statistically significant differences in relation to total Health Related Quality of Life (p-value =0.02) and the impact domain (p-value =0.009). However, the impact domain was more compromised. Diabetes-related complications (p-value =0.004), number of hospitalizations (p-value =0.01), number of daily insulin injections (p-value =0.02), glycated hemoglobin (p-value =0.002) and triglycerides (p-value =0.03) were associated with greater impairment of quality of life related to total health and greater dissatisfaction. Conclusion: Single male adolescents with lower level of education and high glycated hemoglobin levels were more likely to have lower health-related quality of life.